Was the Emergence of the International Gold Standard Expected? Melodramatic Evidence from Indian Government Securities - Marc Flandreau; Kim Oosterlinck (European Historical Economics Society (EHES), 2011)
The emergence of the gold standard has for a long time been viewed as inevitable. Fluctuations of the gold-silver exchange rate in world markets were accused to lead to brutal and unsustainable switches of bimetallic countries' money supplies. However, more recent work has shown that the option character of bimetallism provided a stabilizing feedback loop. Using original data, this paper provides support to the new view. Using quotation prices for Indian Government bonds, we analyze agents' expectations between 1860 and 1890. The intuition is that the spread between gold and silver bonds issued by the same entity (India) and backed by a credible agent (Britain) is a "pure" measure of the silver risk. The analysis shows that up until 1874 markets were expecting bimetallism to last. It is only after this date that markets gradually started requiring a premium to hold silver bonds indicating their belief that gold would eventually become the only metallic standard.
Keywords: F33; N20; 330; Exchange rate regime; gold standard; bimetallism; credibility; silver risk